Realidad de las comunidades rurales de Costa Rica - Bonilla Houdelatth, Erika (2008)
The purpose of this article is to reflect about current reality experimented in rural communities in our country in order to look for solutions to their problems that allow them to reach a better quality of life. Analyses are made from different perspectives. Within this context, we take into account the role that rural communities have in the development of a country as well as the part education plays in the fight for the achievement of a better quality of life.